Rethinking monopoly as a power relation: The shift from market to intellectual monopoly - Cecilia Rikap (City, University of London, City Political Economy Research Centre (CITYPERC), 2023)
The critical literature on monopolies, from monopoly capital to recent contributions, focuses on the organization that concentrates either market power, capital or property rights. I complement this literature by conceptualizing monopolies as a power relation, which enables me to integrate different ways in which the term is used, from capitalists' monopoly over the means of production to intellectual monopolization. As I explain here, some firms have developed greater capacities to systematically monopolize intangibles that are essential for organizing labour beyond their owned assets and for controlling demand. Coupled with institutional, political and technological changes, larger absorptive and management capacities to produce and capture knowledge and information resulted in firms' technological differentiation. The systematic winners of the innovation race hold persistent intellectual monopolies while other firms become subordinate due to their lack of technical autonomy. From this perspective, (intellectual) monopoly power is essential for understanding the distribution of value in capitalism.
Keywords: L12; O34; 330; monopoly capital; power relation; intellectual monopoly; subordinate firms; valuecapture